The Role of Dicer Protein Partners in the Processing of MicroRNA Precursors - Koscianska, Edyta (Public Library of Science, 2011)
One of the cellular functions of the ribonuclease Dicer is to process microRNA precursors (pre-miRNAs) into mature microRNAs (miRNAs). Human Dicer performs this function in cooperation with its protein partners, AGO2, PACT and TRBP. The exact role of these accessory proteins in Dicer activity is still poorly understood. In this study, we used the northern blotting technique to investigate pre-miRNA cleavage efficiency and specificity after depletion of AGO2, PACT and TRBP by RNAi. The results showed that the inhibition of either Dicer protein partner substantially affected not only miRNA levels but also pre-miRNA levels, and it had a rather minor effect on the specificity of Dicer cleavage. The analysis of the Dicer cleavage products generated in vitro revealed the presence of a cleavage intermediate when pre-miRNA was processed by recombinant Dicer alone. This intermediate was not observed during pre-miRNA cleavage by endogenous Dicer. We demonstrate that AGO2, PACT and TRBP were required for the efficient functioning of Dicer in cells, and we suggest that one of the roles of these proteins is to assure better synchronization of cleavages triggered by two RNase III domains of Dicer.